Challenges of electric vehicles urban transport application - Šaban, Andrija; Rauker, Josip; Bekčec, Mihael (Crisis Management Days, 2024)
As environmental protection becomes a general social narrative, many unverified claims may appear in various popular periodicals, instead of an engineering approach to technical issues and an assessment of practice. One of such assessments and claims is that electric vehicles do not pollute the environment and have no impact on climate change. This paper aims to show how electric vehicle technology also has an impact on the environment and lists several challenges that need to be successfully resolved, so that electric vehicles are accepted and truly represent vehicles with an alternative drive.